ChemInform Abstract: Evaluation of Baylis—Hillman Routes to 3‐(Aminomethyl)coumarin Derivatives. Issue 24 (2nd June 2014) - Olasupo, Idris; Rose, Nathan R.; Klein, Rosalyn; Adams, Luqman A.; Familoni, Oluwole B.; Kaye, Perry T.
Abstract Two different Baylis—Hillman approaches for the synthesis of coumarin derivatives containing peptide‐like side chains are investigated.